A Proposed Modeling Method in Finite Element Slope Stability Analysis - A. Asakereh; H. Bazazzadeh (Numerical Methods in Civil Engineering)
Limit-equilibrium method (LEM) and finite element method (FEM) with strength reduction method (SRM) techniques are the most widely used analysis tools in slope stability assessment. Recently, researchers have reported that both factor of safety (FOS) values and failure surfaces obtained from LEM and FEM are generally in good agreement, except in some particular cases. In this paper, the FOS and the location of critical failure surfaces procured by FE-SRM with various modeling types are compared. Eventually, the outcomes of FE-SRM with high mesh density are assumed as reference. The results of this study demonstrated that in FEM, determining the shear band zone by primary analysis of slopes with coarse meshes and consequently modifying the mesh configuration by imposing the program to locate the nodes in that zone can provide accurate and low-cost results. In addition, the comparison between the results of the proposed method and Bishop’s simplified approach as a limit equilibrium method (LEM) represented good agreement and it was evident that better results can be achieved with less cost and time.